Recovery of acidified lakes in Finland and subsequent responses of perch and roach populations - Rask, Martti; Vuorenmaa, Jussi; Nyberg, Kari; Tammi, Jouni; Mannio, Jaakko; Olin, Mikko; Kortelainen, Pirkko; Raitaniemi, Jari; Vesala, Sami (Finnish Environment Institute, 2016)
Finnish-lake and fish-status surveys indicated that 4900 small headwater lakes suffered from acidic deposition and 1600–3200 roach (Rutilus rutilus) and perch (Perca fluviatilis) populations were affected or extinct by the end of 1980s. Since the late 1980s, successful sulphur emission reductions in Europe have induced a chemical recovery of acidified lakes. This resulted in decreases in sulphate and labile aluminium concentrations and increases in pH and alkalinity during the 1990s. The first signs of recovery in affected perch populations were observed in the early 1990s. New strong year-classes appeared and the population structure returned to normal. Little if any recovery of the affected populations of the more acid-sensitive species, roach, was recorded. This may have been due to still critical water quality conditions for successful reproduction of sensitive roach and/or organic acid episodes in the 2000s, suppressing the recovery of buffering capacity. Peer reviewed